1978
DOI: 10.1159/000250926
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentered Study of Lysine Therapy in Herpes simplex Infection

Abstract: Lysine appears to suppress the clinical manifestations of herpesvirus infection. 45 patients with frequently recurring herpes infection were given 312–1,200 mg of lysine daily in single or multiple doses. The clinical results demonstrated a beneficial effect from supplementary lysine in accelerating recovery from herpes simplex infection and suppressing recurrence. Tissue culture studies have demonstrated an enhancing effect on viral replication when the amino acid ratio of arginine to lysine favors arginine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 14 publications
0
72
0
Order By: Relevance
“…The safety record of Lys use in humans is established (47), with most supplemental Lys being used to suppress herpes simplex (48) and to raise the biological value of dietary protein (10,49). Although it is too early to leap from rodent studies to the implications in humans, our data propose a therapeutic use of Lys in the treatment of stress-related intestinal disorders, in which 5-HT sensitization and concurrent anxiety disorder are diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…The safety record of Lys use in humans is established (47), with most supplemental Lys being used to suppress herpes simplex (48) and to raise the biological value of dietary protein (10,49). Although it is too early to leap from rodent studies to the implications in humans, our data propose a therapeutic use of Lys in the treatment of stress-related intestinal disorders, in which 5-HT sensitization and concurrent anxiety disorder are diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Restric tion of dietary L-arginine in subjects prone to recurrent HSV lesions and supplementa tion of the diet with L-lysine may reduce herpes recurrence [3]. Clinical trials in 45 subjects with persistent recurring herpes in fections [4] showed encouraging evidence to support the use of L-lysine supplementation to inhibit HSV attacks. L-Lysine pro phylaxis in recurrent herpes labialis was evaluated in a double-blind crossover clini cal study [5].…”
Section: Discussionmentioning
confidence: 99%
“…Both McCune [8] and Griffith [4] showed no carry-over effect after stopping the L-lysine. Within 1-2 weeks after stopping the L-lysine prophylaxis, many of the subjects had a recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral administration of L-Iysine was reported effective in the treatment of HSV cutaneous infection on the basis of an uncontrolled clinical study [Griffith et al, 1978], Adenine arabinoside, for infusion, is approved in the United States for treatment of HSV-induced encephalitis.…”
Section: Introductionmentioning
confidence: 99%